1999
DOI: 10.1046/j.1365-2923.1999.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardized patients in the early acquisition of clinical skills

Abstract: We conclude that this new model is feasible, was well received by the students and that the reduced tutor to student ratio and lack of inpatient encounters did not appear to adversely affect their learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 7 publications
2
59
0
4
Order By: Relevance
“…A review of published single interview assessment tools revealed a number of instruments for consideration (Arthur 1999, McGraw and O'Connor 1999, Norcini et al 2003, Silverman et al 2011, Stillman, Sabers, and Redfield 1976, Stillman et al 1977, Zraick, Allen, and Johnson 2003. Table 1 provides details of each of these tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of published single interview assessment tools revealed a number of instruments for consideration (Arthur 1999, McGraw and O'Connor 1999, Norcini et al 2003, Silverman et al 2011, Stillman, Sabers, and Redfield 1976, Stillman et al 1977, Zraick, Allen, and Johnson 2003. Table 1 provides details of each of these tools.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the majority of the other tools were developed for use by SPs in assessing students rather than for use by CEs, and primarily for summative assessment (Arthur 1999, McGraw and O'Connor 1999, Stillman, Sabers, and Redfield 1976, Stillman et al 1977. Boulet et al (2008) reported that performance in SP interviews for development of history-taking and physical examination skills is typically assessed by the SP.…”
Section: Introductionmentioning
confidence: 99%
“…Standardisierte Patienten werden als hochgradig realistisch wahrgenommen und sind idealerweise darü ber hinaus im Stande, den Trainingsteilnehmern ein professionelles und strukturiertes Feedback zu geben, in welchem sie Ihre Eindrü cke zur Arzt-Patienten-Interaktion und den hierbei aufgetretenen Gefü hlen und Ü bertragungsreaktionen vermitteln [11]. Wä hrend standardisierte Patienten bisher weitgehend fü r das Training kommunikativer Fertigkeiten und kö rperlicher Untersuchungstechniken genutzt wurden [11,12], finden sie zunehmend Einzug in komplexere Simulationsszenarien im Bereich der Vermittlung manuell-technischer Fertigkeiten [9] oder der Simulation von Stationsvisiten [13]. Rollenspiel bei der Simulation mit computergesteuerten Patientensimulatoren (Erwachsene, Kinder und Sä uglinge) [14], erlaubt es, authentische Lernumgebungen zu schaffen [4].…”
Section: Rollenspiel In Unterschiedlichen Simulationssettingsunclassified
“…Standart hastalar, 1960'larda Howard Barrows'un tanıtmasından bu yana, sağlık personelinin iletişim becerileri de dahil olmak üzere klinik becerilerinin eğitiminde kullanılmaktadır (6). Standart hastaların klinik becerilerin kazanılıp kazanılmadığının güvenilir bir şekilde değerlendirilmesini sağlayabileceğine dair geniş bir kabul bulunmaktadır (3,(7)(8)(9).…”
Section: Introductionunclassified